A Semiotic Analysis on Confession of a Shopaholic Trailer: Roland Barthes Approach - Nur Syasya Qistina Mazeree; Norhakimin Ashaari; Nadzirah Munirah Ramli; Nur Arifah Zahiah Zuri (LET: Linguistics, Literature and English Teaching Journal, 2023)
Deciphering the signals in a movie trailer is undertaken to comprehend how viewers or learners receive the conveyed meanings. The objective of this study is to (1) analyze the symbols present in the "Confession of a Shopaholic" movie trailer and (2) disclose the description of denotation, connotation and myth in the “Confession of a Shopaholic” movie trailer. The primary dataset for this study was the trailer for the film 'Confession of a Shopaholic'. This study employed Roland Barthes' theoretical framework to analyze and establish connections between the signs and the narrative of the trailer. The use of the Barthes approach facilitates the examination of dynamic communication in audio-visual content, and a semiotic analysis was conducted to accomplish the predetermined goals of this study. The research identified a total of six pieces of data included in the trailer and provided detailed explanations of their denotation, connotation, and mythological significance. The study of signals and myths in this research aims to bridge the gap between the established framework and other audio-visual media. Although signals in other domains are important as well, it is highly recommended to do a more comprehensive analysis just on movie trailer outcomes for comparative purposes.